Convergent synthesis, drug target prediction, and docking studies of new 2, 6, 9‐trisubstituted purine derivatives. (4th October 2021) - Villegas, Alondra; Satheeshkumar, Rajendran; Ballesteros‐Casallas, Andrés; Paulino, Margot; Castro, Alejandro; Espinosa‐Bustos, Christian; Salas, Cristian O.
Abstract: A set of new 2, 6, 9‐trisubstituted purine derivatives were designed and synthesized from 6‐chloro‐2‐fluoro‐9‐alkyl‐9 H ‐purine as the key starting material. These purines were synthesized via a multistep protocol and finally subjected to SN Ar with various aminopiperidinyl salts. The structures of these compounds were established by substantiating them through spectral techniques like FT‐IR, 1 H‐NMR, 13 C‐NMR, and 19 F‐NMR. In addition, for two purine derivatives, a reverse screening strategy based on ligand similarity (PharmMapper web server) resulted in a set of predicted protein target candidates. Interestingly, for both purines, the main potential target candidates belonged to key proteins involved within signaling pathways that are related to proliferation or survival of cancer cells. These proteins correspond mainly to enzymes and specifically kinases. To check if our purines could be ligands for two kinases involved in cancer, docking studies were performed. The results indicated that these purines fitted in the same cavity of crystalized inhibitors. Therefore, in this work we are developed new purine derivatives that could be good inhibitors of some kinases. Abstract :